2018
DOI: 10.1097/igc.0000000000001201
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Ubiquitin C-terminal Hydrolase L1 Is Associated With Poor Prognosis in Endometrial Cancer Patients

Abstract: The results of this study suggest that high UCHL1 expression is a strong marker of poor prognosis of endometrial cancer. Furthermore, we suggest that UCHL1 may be involved in the development of distant metastasis in endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…This raises the possibility that the increase in PADI2 we observe is a response to increased UCHL1 protein expression, or vice versa. While our research was ongoing, increased UCHL1 RNA expression was shown to be prognostic for poor overall survival for serous EC patients, 41 a result previously shown in a cohort of mostly endometrioid EC patients 42 . Immunohistochemical expression of UCHL1 in serous ECs and reduced proliferation and cell cycle progression with UCHL1 silencing were also published in this same report 41 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This raises the possibility that the increase in PADI2 we observe is a response to increased UCHL1 protein expression, or vice versa. While our research was ongoing, increased UCHL1 RNA expression was shown to be prognostic for poor overall survival for serous EC patients, 41 a result previously shown in a cohort of mostly endometrioid EC patients 42 . Immunohistochemical expression of UCHL1 in serous ECs and reduced proliferation and cell cycle progression with UCHL1 silencing were also published in this same report 41 .…”
Section: Discussionsupporting
confidence: 64%
“…While our research was ongoing, increased UCHL1 RNA expression was shown to be prognostic for poor overall survival for serous EC patients, 41 a result previously shown in a cohort of mostly endometrioid EC patients. 42 Immunohistochemical expression of UCHL1 in serous ECs and reduced proliferation and cell cycle progression with UCHL1 silencing were also published in this same report. 41 Our results provide the additional novel insight that UCHL1 expression is affected by FBXW7 mutation.…”
Section: Discussionmentioning
confidence: 52%
“…What appeals to us is that despite participation in glucose metabolism, PYCR1 also plays a role in proline metabolism [39] and thus it's worth more comprehensive insights into its molecular functions. Different from PYCR1, whether UCHL1 is an oncogene or a tumor-suppressor depends on types of cancer [40][41][42][43][44]. However, similar to our findings, an article indicated that prognosis of renal cell carcinoma was associated with alterations of UCHL1 promoter methylation [44].…”
Section: Discussionsupporting
confidence: 83%
“…CRABP1 is a retinoic-acid-binding protein, the increased expression of which has already been associated with bad prognosis and increased proliferation in endometrioid endometrial carcinoma [40]. The product of the UCHL1 gene, ubiquitin C-terminal hydrolase L1, has been described as a key player in the metastases formation of tumors in most tumor types, thus also in endometrial carcinoma [41]. FOXB1 is a DNA-binding transcription factor protein the specific role of which has not yet been examined in the tumorigenesis of the endometrium [40,42].…”
Section: Discussionmentioning
confidence: 99%